Does Informal Sector Suitable for Female Labor? - Yuniashri, Erlyn; Susilo, Susilo; Wahyudi, Setyo Tri (JEJAK: Jurnal Ekonomi dan Kebijakan, 2023)
The existence of SDGs program which supported by the demographic bonus era provides potential for female labor force, but the fact in Indonesia is that there is an inequality in the number of working female labor force compared to men, especially the field of work dominated by women is threatened by industrial automation 4.0.  The purpose of this study is to analyze how the characteristics of women to the opportunities in the informal and formal job that seen from age, marital status, wages, length of education taken, ethnicity, and area of residence. The method used in this study is binary logistic regression with IFLS 5 data sources. The results showed that women who decided to work in the informal sector were women of older age, married women, women who studied longer, women with Batak and Sasak ethnicities, and women who lived in rural areas.  The Indonesian government is expected to be able to improve policies for informal sector workers including decent wages,  social security and health, and legal protection in order to achieve Indonesian goals according to SDGs agenda.